Experimental Investigations on Tilting Pad Journal Bearings - Renato Brancati; Stefano Pagano; Ernesto Rocca; Michele Russo; Riccardo Russo (International Journal of Rotating Machinery)
The results of a survey conducted on an experimental system consisting of a rigid rotor supported on two radial bearings each with five tilting pads is presented. In particular, the system was set up in order to assess the dynamic behaviour of the bearing in unusual operating conditions. The response of the bearing to different unbalance values was determined after acquiring and analysing the orbits described by the journal axis for assigned unbalance values in different operating conditions. Analysis of the results shows some particular operating features that were not entirely predicted by the theoretical model and which may give rise to malfunctions in the rotor-tilting pad bearings system. The tests were carried out in the rotor dynamics laboratory of the Dipartimento di Ingegneria Meccanica per l'Energetica at the University of Naples.